Pakistan's Radioactive Decade : An Informal Cultural History of the 1970s - Niilofur Farrukh; Amin Gulgee; and McCarry, John (Karachi Oxford University Press, 2019)
Pakistan's Radioactive Decade' focuses on the cultural output of the 1970s, the most momentous ten years in the nation's history. The book examines the unprecedented experimentation that occurred in a diverse range of fields, including art, dance, music, television, fashion and advertising, among others. 0Over forty writers present their reflections of the national scene. The book also includes the interviews of many iconic figures from the 1970s. The catalyst for the book was an exhibition by the same title held at Amin Gulgee Gallery in March 2016. Co-curators Niilofur Farrukh and Amin Gulgee commissioned 47 artists of different ages to create work inspired by this pivotal decade. These visual acts of remembering and reflecting are included in the book as well. 0'Pakistan's Radioactive Decade' serves as a testimony of the times. Voices of the nation have shared their memories of this vibrant and turbulent decade-an era which older generations reminisce over and the younger generation strives to comprehend. 0'Cultural Polaroids of the Decade' -Amin Gulgee
Include Color Illustrations and Index
Keywords: Manners and customs -- Nineteen seventies -- Art and society -- Artists -- Intellectual life